Land Suitability Evaluation of Coffee in Tokunoshima Island, Japan - Endar Hidayat; Asmak Afriliana; Gusmini Gusmini; Hiroyuki Harada (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2020)
Japan is the 3rd largest importer and consumer of coffee in the world. Considering have many demands of coffee, Japan is looking alternatives for improving to growing and the productivity of coffee. The research was aimed to assessment land suitability class for (arabica and robusta) coffee and land suitability evaluation of coffee. 3 soil samplings were collected from the study area. Matching method is used to evaluate the land suitability with parameter: temperature, elevation, rainfall, slope, pH, and nitrogen. The results showed that climate and physical condition of land area very suitable to grow robusta crops, and its level appropriateness is S1 (highly suitable). However, typhoon is problem in every year for growing coffee crops, but it can be handling by planting protecting crops.